![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{1}{3}x+\frac{2}{5}x+\frac{2}{5}=0\Leftrightarrow\frac{11}{15}x=-\frac{2}{5}\Leftrightarrow x=-\frac{6}{11}\)
b) \(\Leftrightarrow\left(\frac{43}{8}+x-\frac{173}{24}\right).-\frac{3}{50}=1\Leftrightarrow\frac{-11}{6}+x=-\frac{50}{3}\Leftrightarrow x=-\frac{37}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\Rightarrow12x-91=101\\ \Rightarrow12x=192\\ \Rightarrow x=16\\ b,\Rightarrow x:23+45=133\\ \Rightarrow x:23=88\\ \Rightarrow x=\dfrac{88}{23}\\ c,\Rightarrow\left(6x-39\right):7=3\\ \Rightarrow6x-39=21\\ \Rightarrow6x=60\\ \Rightarrow x=10\\ d,\Rightarrow3x-24=\dfrac{148}{73}\\ \Rightarrow3x=\dfrac{1900}{73}\\ \Rightarrow x=\dfrac{1900}{219}\\ e,\Rightarrow\left[{}\begin{matrix}x=0\\x=10\end{matrix}\right.\\ f,\Rightarrow\left[{}\begin{matrix}x=-1\\x=2\end{matrix}\right.\\ d,\left(9-x\right)^3=64=4^3\\ \Rightarrow9-x=4\\ \Rightarrow x=5\\ h,\Rightarrow x=27\\ i,\Rightarrow6x=312\cdot12=624\cdot6\\ \Rightarrow x=624\\ j,\Rightarrow\left(19x+104\right):14=25-42=-17\\ \Rightarrow19x+104=-238\\ \Rightarrow19x=-342\\ \Rightarrow x=-18\)
![](https://rs.olm.vn/images/avt/0.png?1311)
A,-16+23+x=-16
<=>x=-16+16-23
<=>x=-23
B,10-2(4-3x)=-4
<=>10-8+6x=-4
<=>6x=-4-10+8
<=>6x=-6
<=>x=-1
C,-12+3(-x+7)=-18
<=>-12-3x+21=-18
<=>-3x=-18+12-21
<=>-3x=-27
<=>x=9
D,24:(3x-2)=-3
<=>24/(3x-2)=-3
<=>-3(3x-2)=24
<=>3x-2=-8
<=>3x=-6
<=>x=-2
E,|x+8|-7=8
<=>|x+8|=15
<=>x+8=+-15
Chia 2 TH:
TH1:x+8=15
<=>x=7
TH2:x+8=-15
<=>x=-23
F,-45:5(-3-2x)=3
<=>-9(-3-2x)=3
<=>27+18x=3
<=>18x=-24
<=>x=-4/3
G,|x-1|=0
<=>x-1=0
<=>x=1
H,-13|x|=-26
<=>|x|=2
<=>x=+-2
a) -16 + 23 + x = -16
x = -16 + 16 - 23
x = -23
Vậy x = -23
b) 10 - 2. (4 - 3x) = -4
10 - 2 . 4 + 2. 3x = -4
10 - 8 + 6x = -4
6x = -4 - 10 + 8
6x = -6
x = (-6) : 6
x = -1
Vậy x = -1
c) -12 + 3. (-x + 7) = -18
-12 + 3. (-x) + 3. 7 = -18
-12 + (-3x) + 21 = -18
-3x = -18 + 12 - 21
-3x = -27
x = (-27) : (-3)
x = -9
Vậy x = -9
d) 24 : (3x - 2) = -3
3x - 2 = 24 : (-3)
3x - 2 = -8
3x = -8 + 2
3x = -6
x = (-6) : 3
x = -2
Vậy x = -2
e) lx + 8l - 7 = 8
lx + 8l = 8 + 7
lx + 8l = 15
\(\Rightarrow\hept{\begin{cases}x+8=15\\x=18-5\\x=13\end{cases}hay\hept{\begin{cases}x+8=-15\\x=-15-8\\x=-23\end{cases}}}\)
Vậy \(x\in\left\{13;-23\right\}\)
f) (-45) : 5. (-3 - 2x) = 3
(-9). (-3 - 2x) = 3
(-9). (-3) + 9. 2x = 3
27 + 18x = 3
18x = 3 - 27
18x = -24
x = (-24) : 18
x =\(\frac{-4}{3}\)
Vậy x =\(\frac{-4}{3}\)
g) lx - 1l = 0
\(\Rightarrow x-1=0\)
x = 0 + 1
x = 1
Vậy x = 1
h) (-13). lxl = -26
lxl = (-26) : (-13)
lxl = 2
\(\Rightarrow x=2\)
Vậy x = 2
Chúc bạn học tốt!!!
![](https://rs.olm.vn/images/avt/0.png?1311)
a)(2x+4).8-40=24
(2x+4).8=24+40
(2x+4).8=64
2x+4=64:8
2x+4=8
2x=8+4
2x=12
x=12:2
x=6
b)(2x+42)-8=64:2
(2x+16)-8=32
2x+16=32+8
2x+16=40
2x=40-16
2x=24
x=24:2
x=12
c)(3x+2).4-20=24
(3x+2).4=24+20
(3x+2).4=44
3x+2=44:4
3x+2=11
3x=11-2
3x=9
x=9:3
x=3
![](https://rs.olm.vn/images/avt/0.png?1311)
a:x=3/5-7/8=24/40-35/40=-11/40
b: =>1/3:(2x-1)=-1/6
=>2x-1=-2
=>2x=-1
=>x=-1/2
c: =>x-3/4=17/2+7/4=34/4+7/4=41/4
=>x=11
d: =>3x+2=0 hoặc 2/5x+7=0
=>x=-2/3 hoặc x=-7:2/5=-35/2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(8^x+2^{3x}+1=24\)
\(\Rightarrow2^{3x}+2^{3x}=23\)
\(\Rightarrow2^{3x+1}=23\)
đến đây bó tay!